Yā kat kū - Kanlayānō, Phikkhu, 1949- (Tō̜. Bāng Lēn, ʻŌ̜. Bāng Yai, Čhō̜. Nonthaburī [Thailand] : Wat Sūan Kǣo, 1989)
Discourses on Buddhist didactic stories.
In Thai.
Keywords: Religious life -- Buddhism